Intestinal Parasitic Infections among HIV-Infected Patients on Antiretroviral Therapy Attending Debretabor General Hospital, Northern Ethiopia: A Cross-Sectional Study - Alemayehu E (Dove Medical Press, 2020)
Ermias Alemayehu,1 Alemu Gedefie,1 Aderaw Adamu,1 Jemal Mohammed,1 Brhanu Kassanew,2 Berhanu Kebede,3 Melaku Ashagrie Belete1 1Department of Medical Laboratory Science, College of Medicine and Health Sciences, Wollo University, Dessie 1145, Ethiopia; 2Department of Medical Laboratory Science, College of Medicine and Health Sciences, Woldia University, Woldia, Ethiopia; 3Department of Medical Laboratory Science, College of Medicine and Health Sciences, Semera University, Semera, EthiopiaCorrespondence: Melaku Ashagrie Belete; Alemu GedefieDepartment of Medical Laboratory Science, College of Medicine and Health Sciences, Wollo University, Dessie 1145, EthiopiaTel +251-9-1386-7849; +251- 918106000Fax +251 333115250Email melakuashagrie@gmail.com; alemugedefie@gmail.comBackground: Parasitic infections are known causes of morbidity among HIV-infected patients with low CD4+ counts who are on antiretroviral therapy (ART), mainly as a result of immuno suppression. This study aimed to assess the extent of intestinal parasitic infection and related risk factors among HIV-infected patients attending ART clinic at Debretabor General Hospital, Northern Ethiopia.Methods: A health facility–based cross-sectional study was conducted on 383 HIV-infected patients attending the ART clinic of Debretabor General Hospital, northern Ethiopia from December 2018 to March 2019. An interview-based structured questionnaire was used to gather sociodemographic and risk-factor data. About 5 g fresh stool and 4 mL venous blood were collected from each patient, then transported and tested in accordance with laboratory-standard operating procedures. Data obtained were entered into SPSS version 22.0 and analyzed. P< 0.05 with 95% CI was considered statistically significant.Results: The overall prevalence of intestinal parasites was 25.3%, with 18% and 23.8% by direct wet-mount and formol ether–concentration technique, respectively. Eight (2.1%) patients were infected by multiple parasites using the concentration technique. Ascaris lumbricoides was the most frequently identified parasite (n=23, 25.3%). Parasitic infection was significantly higher among illiterates (P= 0.011), patients with CD4 count < 200 cells/mm3 (P< 0.001), and those who did not have a toilet in their home (P= 0.049) than their counterparts.Conclusion: Relatively higher prevalence of intestinal parasitic infection was found among HIV/AIDS patients. The distribution of intestinal parasites was greatly affected by illiteracy, reduced CD4+ counts, and absence of a toilet. Therefore, HIV/AIDS patients with low CD4+ counts should be diagnosed consistently for intestinal parasites with routine stool examinations, and awareness creation should be advocated to be included as an essential component of ART-monitoring strategies for improved patient care.Keywords: antiretroviral therapy, debretabor, HIV/AIDS, intestinal parasites, risk factors